Development of a Participatory Strategic Management Model for Collaborative Educational Provision Schools - Manketvit, Supapron; Srisa-ard, Boonchom; Setsaengsri, Charnon (The Journal of Behavioral Science, 2016)
Small schools in remote areas throughout Thailand need to utilize effective management approaches to enable them to tackle problems that result in low educational quality. This study aimed to develop a participatory strategic management (PSM) model for small school groups, known as Collaborative Educational Provision (CEP) schools that are under the Office of the Basic Education Commission of the Ministry of Education. The methodology used was research and development (R&D) with quantitative and qualitative mixed methods. The PSM model developed was tested utilizing purposive sampling of a group of 4 CEP schools in a district of Chiang Mai and including 4 administrators, 22 teachers, 10 school committee members, 20 parents, and 10 community leaders. The PSM model developed consisted of 4 components with 65 indicators. The four components were participatory in character, and consisted of strategic analysis, strategic planning, strategic implementation, and strategic control and evaluation. After implementation of this PSM model, findings showed that all five of the CEP personnel sampled agreed to a higher level of work practice. They also expressed strong satisfaction with the implementation of the trial model. In particular, this model, focusing on a participatory approach, was able to solve many problems related to small schools, especially teacher shortages.